Study Protocol: The Coaching Alternative Parenting Strategies (CAPS) Study of Parent-Child Interaction Therapy in Child Welfare Families - Nekkanti, Akhila K.; Jeffries, Rose; Scholtes, Carolyn M.; Shimomaeda, Lisa; DeBow, Kathleen; Norman Wells, Jessica; Lyons, Emma R.; Giuliano, Ryan J.; Gutierrez, Felicia J.; Woodlee, Kyndl X.; Funderburk, Beverly W.; Skowron, Elizabeth A. (Frontiers in Psychiatry, 2020)
Background: Child maltreatment (CM) constitutes a serious public health problem in the United States with parents implicated in a majority of physical abuse and neglect cases. Parent-Child Interaction Therapy (PCIT) is an intensive intervention for CM families that uses innovative ‘bug-in-ear’ coaching to improve parenting and child outcomes, and reduce CM recidivism; however, the mechanisms underlying its effects are little understood. The Coaching Alternative Parenting Strategies (CAPS) study aims to clarify the behavioral, neural, and physiological mechanisms of action in PCIT that support positive changes in parenting, improve parent and child self-regulation and social perceptions, and reduce CM in child welfare-involved families. Methods: The CAPS study includes 204 child welfare-involved parent-child dyads recruited from Oregon Department of Human Services to participate in a randomized controlled trial of PCIT versus a services-as-usual control condition (clinicaltrials.gov, NCT02684903). Children ages 3-7 years at study entry and their parents complete two waves of assessment: a baseline and post-intervention assessment at roughly 9-12 months post-study entry. Each wave includes individual and joint assessment of parents’ and children’s cardiac physiology at rest, during experimental tasks, and in recovery; observational coding of joint parent-child interactions; and individual electroencephalogram (EEG) sessions including attentional and cognitive control tasks. In addition, parents and children complete an emotion regulation task and parents report on their own and their child’s adverse childhood experiences and socio-cognitive processes, while children complete a cognitive screen and a behavioral measure of inhibitory control. Parents and children also provide anthropometric measures of allostatic load and 4-5 whole blood spots for assessment of inflammation and immune markers. Dyads randomized to the intervention condition also complete an abbreviated mid-intervention assessment. CM recidivism is assessed for all study families at 6-months post-intervention. Post-intervention and follow-up assessments are currently underway. Discussion: Knowledge gained from this study will clarify PCIT effects on neurobehavioral target mechanisms of change in predicting CM risk reduction, positive, responsive parenting, and children’s outcomes. This knowledge can help to guide efforts to tailor and adapt PCIT to vary in dosage and cost on the basis of individual differences in CM-risk factors.